2010
DOI: 10.1089/tmj.2009.0156
|View full text |Cite
|
Sign up to set email alerts
|

E-health Applications and Services for Patient Empowerment: Directions for Best Practices in The Netherlands

Abstract: Objective: E-health may enable the empowerment process for patients, particularly the chronically ill. However, e-health is not always designed with the requirements of patient empowerment in mind. Drawing on evidence-based e-health studies, we propose directions for best practices to develop e-health that promotes patient empowerment. Methods: The concept of patient empowerment in the Dutch setting is discussed first. The prerequisites for patient empowerment are then described and translated into empowerment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 11 publications
3
74
0
2
Order By: Relevance
“…Our findings support previous studies, which report that empowerment can be improved by using digitized approaches in healthcare [5,37,41]. Empowerment implies participation and responsibility through increased awareness and knowledge [42].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings support previous studies, which report that empowerment can be improved by using digitized approaches in healthcare [5,37,41]. Empowerment implies participation and responsibility through increased awareness and knowledge [42].…”
Section: Discussionsupporting
confidence: 90%
“…Alpay et al [37] concluded that in removing barriers of time and geographical distance in healthcare services -by use of digital and technological services such as video consultations and telehealth -the patients gain flexibility. They get an easier and more convenient access to healthcare, they may even have fewer time-demanding healthcare centre visits, and finally, patients can receive care at a location that does not require transportation, and in an environment that can be experienced as less threatening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an evaluation process of the empowerment process, the evaluation of community empowerment can be based on the calculation of individual empowerment. 9 In this sense, professional training aims to train professionals capable of stimulating the local population to act effectively on their living conditions and health and be aware of their rights and how to reach it. Monte Negro has a high percentage of population living in rural areas (60%), and this population cannot easily shift to the city, which happens sporadically, so the education of the CHW is paramount to conducting an active study of the health needs of this population as well as to conduct health promotion activities targeted to their needs.…”
Section: Wjd E-health: a Health Promotion Tool For Brazilian Amazon Rmentioning
confidence: 99%
“…That is, their systems can also function as e-Health technology [19] by functioning as an eCoach (see e.g., [20]), and help users adapt their behavior. Such technology would be Persuasive Technology [1][2][3], as it attempts to change user behavior or attitudes without coercion or deception [1,24].…”
Section: Introductionmentioning
confidence: 99%